Solar Load Ratio and ISO 13790 methodologies: Indirect gains from sunspaces - Panão, Marta Oliveira (2012)
This paper reviews and analyzes the compatibility of the simplified empirical method based on the dimensionless parameter of Solar Load Ratio (SLR) and the monthly procedure of the standard ISO 13790 for indirect gains, specifically for unconditioned zones adjacent to a conditioned zone, but separated from it by a partition wall (sunspaces). The main contribution of the work presented here is the new formulation to account SLR correlations in ISO 13790, obtained for sunspaces, but generalizable for other solar systems with known SLR functions. Simulation models are used to perform a sensitivity analysis of internal gains and heat transfer through solar collector surfaces, both issues that distinguishes ISO 13790 from Load Ratio methods. The analysis shows that internal gains can be added to the heat source term or subtracted to heat transfer term without influencing the utilization factor dependence with the gain-to-loss ratio. On the other hand, the SLR assumption that solar collector surfaces are neutral elements and, therefore, not added to the heat transfer term, results in large inconsistencies between SLR and ISO 13790 methods. The detailed monthly methodology of ISO 13790 fairly reproduces results obtained by simulation. However, predictions from the simplified monthly methodology of ISO 13790 fail in mid season months and coldest months.